Human Resouce Management in the Age of Artificial Intelligence: Concepts Tools and Steps - Awad Mabrouk (Walidem Institute and Publishing, 2025)
Objective: This study examines the transformative role of Artificial Intelligence (AI) in enhancing Human Resource Management (HRM) processes and its contribution to improving organizational efficiency and employee experience. As organizations navigate an increasingly dynamic job market, the integration of AI offers opportunities for achieving sustainable success while addressing the demands of flexibility and innovation. The research aims to identify effective strategies for AI adoption in HRM, focusing on three key dimensions: personalization of employee experiences, security and privacy assurance, and adaptability to continuous technological advancements. Theoretical framework: Grounded in a theoretical framework that highlights the intersection of technology and strategic HRM, the study builds on a comprehensive literature review of recent advancements in AI applications within HRM. Literature Review: The literature underscores the potential of AI to streamline recruitment, talent management, and employee engagement processes, creating a more responsive and efficient HR ecosystem. Methods: A qualitative research method was employed, involving in-depth analyses of case studies and current HRM practices where AI has been integrated. Data were collected from organizational reports, interviews with HR professionals, and academic publications. Results: The findings reveal that AI adoption fosters a strategic advantage by seamlessly integrating technology into various HRM functions, resulting in improved decision-making, enhanced productivity, and higher employee satisfaction. Specifically, AI-driven tools enable HR departments to provide personalized support to employees, anticipate workforce needs, and optimize resource allocation. Implications: The implications of this research emphasize the necessity for organizations to adopt a holistic strategy for AI integration. This strategy should include substantial investments in technology infrastructure, upskilling HR professionals, and fostering an organizational culture that embraces technological innovation. These measures are essential for achieving competitive advantage and enhancing employee experiences in an era dominated by digital transformation. Novelty: The novelty of this study lies in its focus on the strategic vision required to fully integrate AI into HRM. Unlike previous research that often considers AI as a supplementary tool, this study asserts that AI is a foundational component for future business competitiveness. By framing AI as an essential enabler of strategic HRM, this research contributes to a deeper understanding of how technology can redefine organizational operations and create value.